Plasmalogens: targets for oxidants and major lipophilic antioxidants. (1st February 2004) - Engelmann, B.
Abstract : Cellular membranes and plasma lipoproteins are less efficiently protected against oxidative stress than the various aqueous compartments of mammalian organisms. Here, previous results on the role of plasmalogens in lipid oxidation are evaluated on the basis of criteria required for an antioxidant. The plasmalogen-specific enol ether double bond is targeted by a vast variety of oxidants, including peroxyl radicals, metal ions, singlet oxygen and halogenating species. Oxidation of the vinyl ether markedly prevents the oxidation of highly polyunsaturated fatty acids, and products of plasmalogen degradation do not propagate lipid oxidation. This protection is also demonstrated intramolecularly, thus ascertaining the function of plasmalogens as a major storage pool for polyunsaturated fatty acids. Although cells rapidly incorporate and synthesize plasmalogens de novo, their plasmalogen contents can be deliberately increased by supplementation with precursors. Thus plasmalogens terminate lipid-oxidation processes, are present in adequate locations at sufficient concentrations, and are rapidly regenerated, classifying them as efficient antioxidants in vitro . Future work should address the in vivo role of plasmalogens in lipid oxidation and the biological function of plasmalogen interactions with oxidants.